2021
DOI: 10.3390/ijms22179511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Resveratrol and Its Derivatives on the Radiation Response of MCF-7 Breast Cancer Cells

Abstract: Radiotherapy is among the most important methods for breast cancer treatment. However, this method’s effectiveness is limited by radioresistance. The aim of this study was to investigate whether the stilbene derivatives piceid, resveratrol, and piceatannol have a radiosensitising effect on breast cancer cells (MCF-7). The conducted research enabled us to determine which of the tested compounds has the greatest potential in sensitising cells to ionising radiation (IR). Among the stilbene derivatives, resveratro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…First, the concentration range combined with the time course of PD administration is under-considered when detecting cell viability, apoptosis, and some other indicators. For example, different teams presented different views about how PD affects cell apoptosis with different PD concentrations [13,23]. Here, we showed that although multiple apoptosis results did not yield statistically different comparisons, it was still possible to find that PD was attenuating the apoptosis rate of both cell lines after 24 h but increasing it after 48 h, suggesting that its cytotoxic effects may not be mainly dependent on the apoptotic pathway.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…First, the concentration range combined with the time course of PD administration is under-considered when detecting cell viability, apoptosis, and some other indicators. For example, different teams presented different views about how PD affects cell apoptosis with different PD concentrations [13,23]. Here, we showed that although multiple apoptosis results did not yield statistically different comparisons, it was still possible to find that PD was attenuating the apoptosis rate of both cell lines after 24 h but increasing it after 48 h, suggesting that its cytotoxic effects may not be mainly dependent on the apoptotic pathway.…”
Section: Discussionmentioning
confidence: 75%
“…This phenomenon is consistent with another finding when authors compared the effects of resveratrol and its derivatives including PD on the radiation response of breast cancer cells. Though they adopted a different cell line other than lung cancer cells and treated cells with lower concentrations of PD (5 and 25μM), it was shown that, unlike its analogue resveratrol, PD decreased the cell viability without altering apoptosis very much [23]. However, some existing studies showed some non-consistent opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the formation of excessive amounts of ROS characteristic of tumorigenic processes, most cancer cells show increased overexpression of SOD . Furthermore, there are many studies reporting that RES and its derivatives, as well as fatty acids themselves, cause increased ROS accumulation in cancer cells [ 15 , 24 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is consistent with another finding when authors compared the effects of resveratrol and its derivatives including PD on the radiation response of breast cancer cells. Though they adopted a different cell line other than lung cancer cells and treated cells with lower concentrations of PD (5 and 25 μM), it was shown that, unlike its analog resveratrol, PD decreased the cell viability without altering apoptosis very much (Komorowska et al 2021 ). However, some existing studies showed some non-consistent opinions.…”
Section: Discussionmentioning
confidence: 99%